Path loss simulation in different radio propagation models with 1.8 GHz and 2.6 GHz bands - Chariyev, A. (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper presents the simulation of path loss propagation models in LTE-Advanced Networks for suburban and rural areas. Calculations were done using MATLAB based simulation; for various prediction techniques such as Cost 231 Hata Model, Stanford University Interim (SUI) and Ericsson Model. The authors used to analyze the 1800MHz (1.8 GHZ) and 2600MHz (2.6 GHz) wideband channels which are operating bands for Malaysian 4G companies. Results show almost 60dB gap between using COST231 and SUI; and 20dB gap is achieved among COST231 and Ericsson models. The effectiveness of Stanford University Interim Model is also discussed. Â© 2014 IEEE.